The minimally invasive method for treatment of stress urinary incontinence in women - Vera E. Balan; Elena V. Tikhomirova; Marina A. Chechneva; Olga V. Kapitanova; Svetlana A. Orlova; Anastasiya S. Zhuravel; Elena V. Kruchinina; Vasilii A. Petrukhin (LLC "MEDIAFORMAT", 2023)
Urinary incontinence is a complex medical and social problem. Surgical methods designed to treat stress urinary incontinence are expensive and have a number of complications, and existing alternative surgical methods have been ineffective and caused complications due to the very nature of the fillers used. Today, a gel based on hyaluronic acid, DELIGHT® G®, has appeared on the pharmaceutical market, which is injected into the paraurethral area for the purpose of co-opting the urethra. Aim. To develop indications for paraurethral administration of DELIGHT® G® hyaluronic acid-based gel for stress urinary incontinence and to evaluate its effectiveness and safety. Materials and methods. The study involved 35 patients aged 45-55 with mild stress incontinence. Results. The effectiveness of urinary incontinence therapy was 97.1% (n=34). All patients underwent functional tests, uroflowmetry, profilome-try and ultrasound examination of the paraurethral area before and after paraurethral injection of hyaluronic acid-based gel. Uroflowmetry data: before the introduction of the gel, the average value of Qmax 27±1.5 ml/sec and Q average 13.5±2.7 ml/sec, immediately after the paraurethral in-jection of the gel, Qmax 19±2.1 ml/sec and Q average 12.6±1.6 ml/sec and after month Qmax 20±2.3 ml/sec and Q average 11.9±1.9 ml/sec. Profilom-etry data: the average length and functional length of the urethra were 34±0.9 mm and 31±0.8 mm, respectively, which indicates that this study is not informative. According to ultrasound examination of the paraurethral area, after the introduction of a gel based on hyaluronic acid into the paraurethral area, signs of urethral hypermobility and sphincter insufficiency are leveled. Conclusions. Paraurethral injection of hyaluronic acid-based gel can be considered as first-line therapy stress urinary incontinence for patients with initial manifestations of stress urinary incontinence.